2010
DOI: 10.1080/21513732.2010.505011
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces for fuelwood choice of households in developing countries: environmental implications for Bangladesh

Abstract: Energy planning is an important task for every nation. Understanding the energy preferences of households influences a major part of energy planning and policy. In the preference system, socio-economic driving forces act critically, dictating energy use. Thus, the present study was undertaken to understand the socio-economic driving forces for energy preferences in developing countries, considering the Energy Ladder and the environmental Kuznets curve (EKC) hypothesis. Results show that biomass still plays a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
(54 reference statements)
0
11
0
4
Order By: Relevance
“…On the other hand, Campbell et al [26] recommended that the Government of Zimbabwe should question the desirability of encouraging housholds along the energy ladder. In these and other related studies, income played a key role in defining the energy shift from dirty to clean energy sources [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Campbell et al [26] recommended that the Government of Zimbabwe should question the desirability of encouraging housholds along the energy ladder. In these and other related studies, income played a key role in defining the energy shift from dirty to clean energy sources [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Campbell et al [26] recommended that the Government of Zimbabwe should question the desirability of encouraging housholds along the energy ladder. In these and other related studies, income played a key role in defining the energy shift from dirty to clean energy sources [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…In general, two types of studies have been conducted in developing countries. Some studies were observational (e.g., [25][26][27][28]). For instance, Miah et al [9] carried out an exploratory survey on rural and semi-urban households in Bangladesh and concluded that income-generating activities should be encouraging households to "progress" along the energy ladder.…”
Section: Introductionmentioning
confidence: 99%
“…Others documented the shortage of biomass, specifically firewood in forest-rich and degraded areas, due to overexploitation of the resources (Akther et al, 2010b(Akther et al, , 2010cHassan et al, 2014;Miah et al, 2009;Nath et al, 2013). However, according to Hassan et al (2012), little information is available on rural households' energy consumption patterns and their expenditure on various types of energy, quantity, and sources of fuels.…”
Section: Objective (S) Of the Studymentioning
confidence: 99%